(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article explores the dichotomy of “material” and “spiritual” values in American and Uzbek literature. The study focuses on the artistic interpretation of wealth, social status, fame, moral responsibility, dignity, conscience, and spiritual emptiness in selected literary works. In American literature, the issue is analyzed mainly through F. Scott Fitzgerald’s The Great Gatsby and Babylon Revisited, where material prosperity is closely connected with the crisis of the American Dream, moral carelessness, and personal alienation. In Uzbek literature, the same problem is examined through Abdulla Qodiriy’s O‘tkan kunlar, Oybek’s Qutlug‘ qon, Erkin A’zam’s Momoqaldiroq ostida sayr, and Ulugbek Hamdam’s Muvozanat. The article argues that although American and Uzbek literatures belong to different cultural and historical contexts, both traditions reveal that material success loses its value when it is separated from spiritual maturity, ethical responsibility, and human dignity